(untitled) (Training and Practice : Journal of Educational Sciences, 2012)
In this paper the results of the survey among the clerks in the province of Vác will be presented. The aim of the study can be summarize in four major points. First, examine the relationship of the gipsy children with the faith. Secondly, explore the frequency of visiting church service of the gipsy children. Thirdly, examine the attitudes of the clerks related to the gipsy population and the opinion about the divinity of the gipsy children. The analysis and conclusions are based on the answers 24 clerks. The results indicate that the deep of the faith of the gipsy children depends on the friendship with non gipsy children and on the faith of their parents. The negative attitudes of the clerks are related rather to the parents of the gipsy children and not to the gipsy children themselves. As conclusion can be drawn that the establishment such kind of communities where gipsy children learn about the faith together with their parents.